SAMHD1 Promotes DNA End Resection to Facilitate DNA Repair by Homologous Recombination - Daddacha, Waaqo; Koyen, Allyson E.; Bastien, Amanda J.; Head, PamelaSara E.; Dhere, Vishal R.; Nabeta, Geraldine N.; Connolly, Erin C.; Werner, Erica; Madden, Matthew Z.; Daly, Michele B.; Minten, Elizabeth V.; Whelan, Donna R.; et al. (Cell reports (Cambridge), 2017)
DNA double-strand break (DSB) repair by homologous recombination (HR) is initiated by CtIP/MRN-mediated DNA end resection to maintain genome integrity. SAMHD1 is a dNTP triphosphohydrolase, which restricts HIV-1 infection, and mutations are associated with Aicardi-Goutières syndrome and cancer. We show that SAMHD1 has a dNTPase-independent function in promoting DNA end resection to facilitate DSB repair by HR. SAMHD1 deficiency or Vpx-mediated degradation causes hypersensitivity to DSB-inducing agents, and SAMHD1 is recruited to DSBs. SAMHD1 complexes with CtIP via a conserved C-terminal domain and recruits CtIP to DSBs to facilitate end resection and HR. Significantly, a cancer-associated mutant with impaired CtIP interaction, but not dNTPase-inactive SAMHD1, fails to rescue the end resection impairment of SAMHD1 depletion. Our findings define a dNTPase-independent function for SAMHD1 in HR-mediated DSB repair by facilitating CtIP accrual to promote DNA end resection, providing insight into how SAMHD1 promotes genome integrity. [Display omitted] •SAMHD1 deficiency or Vpx-mediated degradation sensitizes cells to DSB-inducing agents•SAMHD1 localizes to DNA double-strand breaks in response to DNA damage•SAMHD1 promotes HR and DNA end resection independent of its dNTPase activity•SAMHD1 complexes with CtIP and facilitates its recruitment to DNA damage sites SAMHD1 is a dNTP triphosphohydrolase, which restricts HIV-1 infection and is dysregulated in Aicardi-Goutières syndrome and cancer. Daddacha et al. define a dNTPase-independent function for SAMHD1 in HR-mediated DSB repair by facilitating CtIP accrual to promote DNA end resection, providing insight into how SAMHD1 promotes genome integrity.